How facilitate reading learning (Journal of Parents and Teachers, 2017)
Although many children learn to read without difficulty, regardless of the  preparation they have had or the method used, each year there are a significant percentage of children who are doomed to failure if no special precautions are taken. There are three key moments in which we must act and can avoid many failures: before beginning the teaching of reading, developing their phonological awareness, during learning, selecting a good method that facilitates the relationship between letters and their corresponding sounds And after learning, automating the decoding processes so that they can devote their cognitive resources to the understanding of what they read.
Keywords: reading learning; phonological awareness; dyslexia; educational guidance